Skyhook Churchill 1972. - White,Paul S.; Pappas,Thomas (1973)
The program was funded to conduct balloon field operations from Fort Churchill, Manitoba, Cape Girardeau, Missouri, and Red Deer, Alberta. The report describes individual flights, equipment used, flight data, and various program information. (Modified author abstract)